Current regionalisation processes in the rhine-main region - Langhagen-Rohrbach, Christian (Raumforschung und Raumordnung | Spatial Research and Planning, 2004)
Far-reaching regional reforms have already been carried out in the Stuttgart and Hanover regions that have proved to be effective. For the Rhine-Main area, on the other hand, a regional structure has been introduced with the Conurbation Act that has been less successful since its introduction in 2001. Instead the debate on how the Rhine-Main region should be structured and which kind of regulation such a polycentric urban agglomeration needs has broken out again. This article attempts to outline current regionalisation processes taking the theoretical approach of action-theoretical social geography as a point of departure and to identify constellations of actors who are currently occupied with developing suggestions for a future- and policy-oriented regional structure in the Rhine-Main area or with asserting their influence in the corresponding debate. In order to do this, different examples of regional initiatives and organisations are presented and questioned critically in terms of their significance and effectiveness.